Leveraging topoisomerase II-mediated DNA damage: repurposing etoposide as a lead compound for apicomplexan parasite control - Li, Yongchang; Cui, Zeyun; Li, Jianlong; Zhang, Yang; Zafar, Iqra; Rizk, Mohamed Abdo; Li, Hang; El-Sayed, Shimaa Abd El-Salam; Yokoyama, Naoaki; Guo, Qingyong; Xuan, Xuenan; Chahan, Bayin (Frontiers in Veterinary Science, 2025)
Babesia and Theileria are microscopic parasites that infect livestock, leading to substantial economic losses. Current treatments are often limited by challenges such as drug resistance and incomplete parasite eradication. This study investigates potential of Etoposide (EP), a well-known anticancer drug that disrupts DNA Topoisomerase II, as a treatment for these parasitic infections. The research focused on EP’s ability to inhibit Babesia bovis, Babesia caballi, and Theileria equi, evaluating its impact on parasite viability, structural changes, and protective role for host red blood cells. Parasites were exposed to various concentrations of EP (ranging from 0.50 × to 4 × IC50), and their viability and morphology were assessed through bioassays and Giemsa-stained slides analysis. In vivo experiments were conducted using a mouse model infected with Babesia microti, to examine changes in parasite burden, red blood cell counts, and fluorescence-based signals. The results demonstrated that EP inhibited parasite growth in a dose-dependent manner, with IC50 values of 11.23 ± 2.82 μM for B. bovis, 0.037 ± 0.039 μM for B. caballi, and 0.68 ± 0.39 μM for T. equi. Importantly, parasites treated with EP did not recover when returned to untreated culture conditions. Morphological changes included distinct spots in B. bovis and B. caballi, along with abnormal structures in T. equi. These findings suggest that EP has potential as a complementary therapy, enhancing the effectiveness of existing treatments for Babesia and Theileria infections. Further research is warranted to refine its application and investigate its role in combination therapy strategies.